MicroRNA-378 is involved in hedgehog-driven epithelial-to-mesenchymal transition in hepatocytes of regenerating liver - Kim, Jieun (Cell Death Dis, 2018)
Healthy livers have a remarkable regenerative capacity for reconstructing functional hepatic parenchyma after 70% partial hepatectomy (PH). Hepatocytes, usually quiescent in normal healthy livers, proliferate to compensate for hepatic loss after PH. However, the mechanism of hepatocyte involvement in liver regeneration remains unclear. Hedgehog (Hh) pathway plays an important role in tissue reconstitution by regulating epithelial-to-mesenchymal transition (EMT) in liver disease. MicroRNA (miRNA) is involved in cell proliferation and differentiation during embryonic development and carcinogenesis. It was recently reported that miR-378 inhibits transdifferentiation of hepatic stellate cells into myofibroblasts by suppressing Gli-Krüppel family member 3 (Gli3), the Hh-target gene. We hypothesized that miR-378 influences EMT in hepatocytes by interfering with Hh signaling during liver regeneration. As hepatocytes were highly proliferative after PH in mice, miR-378 and epithelial marker, Ppar-g or E-cadherin were downregulated, whereas both Hh activators, Smoothened (Smo) and Gli3, and the EMT-inducing genes, Tgfb, Snail and Vimentin, were upregulated in the regenerating livers and in hepatocytes isolated from them. Compared to cells with or without scramble miRNA, primary hepatocytes transfected with miR-378 inhibitor contained higher levels of Gli3 with increased expression of the EMT-promoting genes, Tgfb, Snail, Col1a1, and Vimentin, suggesting that miR-378 influenced EMT in hepatocytes. Smo-depleted hepatocytes isolated from PH livers of Smo-flox mice showed downregulation of EMT-promoting genes and Gli3, with upregulation of miR-378 and E-cadherin compared to Smo-expressing hepatocytes from PH liver. In addition, delivery hepatocyte-specific AAV8 viral vector bearing Cre recombinase into Smo-flox mice impeded EMT in Smo-suppressed hepatocytes of PH liver, indicating that Smo is critical for regulating hepatocyte EMT. Furthermore, the application of miR-378 mimic into mice with PH delayed liver regeneration by interrupting hepatocyte EMT. In conclusion, our results demonstrate that miR-378 is involved in hepatocyte EMT by regulating Hh signaling during liver regeneration.